«Hacéis caciques aunque sea de un palo...» Kurakas ilegítimos y ladinismo en el temprano Perú colonial - Arana Bustamante, Luis (2006)
This essay puts toghether and discusses some early historical evidence about Andean ‘illegitimate’ kurakas from the origins of colonial system to c. 1615. They were appointed to their posts by colonial authorities and the most uncapable in their tasks would cause many disturbances in social indigenous life in colonial times. The main concern is to improve the historical basis for analysis of somewhat confussing archival evidence derivated of conflicts between Andean central Highlands kurakas in administrative and ‘idolatry’ colonial trials.